Penerapan Algoritma Fisher-Yates Shuffle dalam Game Memory Card Sistem Periodik Unsur Kimia Berbasis Android: Implementation of the Fisher-Yates Shuffle Algorithm in an Android-Based Memory Card Game of the Periodic Table of Chemical Elements - Eka Wahyu Hidayat; Firmansyah Maulana Sugiartana Nursuwars; Lita Lestari Utami; Solihin (Jurnal Informatika dan Multimedia, 2026)
Educational games play an important role in supporting the learning process, including in chemistry, a subject often considered difficult by students. One of the main challenges is recognizing and remembering elements in the Periodic Table of Chemical Elements. To address this, this study developed an Android-based educational game in the form of a Memory Card game designed to help students train their memory in recognizing symbols and names of chemical elements. The development method used is the Multimedia Development Life Cycle (MDLC) which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The Fisher-Yates Shuffle algorithm is applied in the game to randomize the card positions, providing variety and a level of challenge in each game session. Testing was carried out in three stages: functionality testing using Boundary Value Analysis (BVA), visual algorithm testing through five iterations to ensure random card distribution, and usability testing using the System Usability Scale (SUS) method. The results of the functionality testing showed that all features ran according to design, the algorithm testing proved that randomization worked well without repetitive patterns, and the usability testing obtained an average score of 76.97, which is included in the good category. Based on these results, it can be concluded that the Periodic Table of Chemical Elements Memory Card game is able to be an interactive and interesting learning medium for students.